Isu Agama dalam Sisdiknas No.20 Tahun 2003: Meninjau Kembali Jalan Demokrasi Pendidikan Nasional - Binsar Antoni Hutabarat (Reformed Center for Religion and Society, 2014)
ABSTRACT:Â This article discusses religious issues and implementation of the National Education System Law (Undang-undang Sistem Pendidikan Nasional or Sisdiknas Law) No.20 of 2003. The presence of Sisdiknas 2003 can not be separated from the power struggles that occur at the time. The ideological debate among the Indonesian elite had not ended, and caused crisis in managing education in Indonesia. As a result, the mobilization of educational resources to achieve the education especially those esthablished by religious institutions. The politicis of education in Indonesia is still dominated by groups interests. Consequently national education law has not appreciated the diversity of Indonesia, and has not become the property of all individuals and groups.Â KEYWORDS:Â national education system (Sisdiknas), religious education, democracy education.